Implementation of Ergonomic Work System for Occupational Diseases in Red Onion Porters in Banjarejo Village - Ahmad Farid Naylul Muwafiq; Mayta Sari Dwianggimawati (Journal of Hospital Management and Services, 2021)
Occupational Safety and Health (K3) issues in general in Indonesia are still often ignored. This is indicated by the still high number of work accidents. In 2014, there were 40,694 cases of Occupational Diseases (PAK) in Indonesia. For this reason, researchers are interested in conducting research on "Implementation of Ergonomic Work Systems on Occupational Diseases in Shallot Porters in Banjarejo Plemahan Village". This study uses the Observational method and cross-sectional study design. With a simple random sampling technique and a sample of 44 respondents was obtained. The results of this study indicate that the ergonomic work system in shallot porters has an effect of 78% on occupational diseases and the other 22% is influenced by other factors that were not studied. It can be concluded that the application of an ergonomic work system has a significant effect on occupational diseases in shallot porters in Banjarejo Plemahan Village.